Beneficiamento em mesa densimétrica e desempenho de sementes de tabaco - Gadotti, Gizele Ingrid (2006)
The disposable information about small seeds, include tobacco, especially about the perform densimetric table, it haven t been contemplate to literature. The present work was carried through with the objective to verify the perform tobacco seeds process in densimetric table. The seeds had initially been clean in air machine. The terminal axle of discharge of the densimetric table of width 50 cm was dividend in five parts: low with 9 cm, low and high intermediate each with 13 cm, high with 15 cm and discharge going out stone with 3 cm. The treatments had constituted of the fraction gotten in the feeding deposit and of the five parts discharged each part of the discharge. This work comprised two studies, the first involved seven combinations of the densimetric table regulations and the second seven tobacco cultivars. Tobacco seeds discharged on the high fraction in densimetric table discharge zone presents superior physiological quality as that seeds in the low fraction. The densimetric table, properly regulated, presents efficiency in the improvement of the physiological quality in the tobacco seeds lots to remove of the fraction discharge in low part zone of discharge.